Oxygen Demand of the Sediment from the Semariang Batu River, Malaysia - Ling, Teck Yee; Ng, Chiat-Siew; L., Nyanti; Dungung, Buda (IDOSI Publication, 2009)
The Semariang Batu River is located near the city of Kuching, with residential and shrimp farming activities which may impact the quality of the sediment. However, sediment of this river had not been investigated. Therefore, the objectives of this study were to determine the sediment oxygen demand (SOD) at different locations along the river and the relationship between SOD and the characteristics of the sediment. Surface sediments were collected at five stations for analysis. Results indicated that sediment total phosphorus values ranged from 288-1446 mg/kg. The station near the residential, seafood and boat landing jetty and the station near shrimp farm discharge recorded the highest sediment phosphorus and nitrogen. SOD ranged from 0.76 gO/m2/day at the station with the least human activities to 21.4 gO/m2/day at the station with shrimp farm discharge. SOD near the jetty was also high 16.2 gO/m2/day which ranked the second highest in value among the five stations. SOD values were significantly correlated with phosphorus, nitrogen and clay content of the sediment.